Live at the Bon Soir [compact disc] - Streisand, Barbra (Columbia ; Legacy Recordings, 2022)
Recorded in November 1962, this album marks the first official release of the legendary Greenwich Village Nightclub shows and includes 24 newly mixed performances from the original master tapes in Barbra's personal collection.